2017
DOI: 10.1002/ase.1677
|View full text |Cite
|
Sign up to set email alerts
|

Using collaborative two‐stage examinations to address test anxiety in a large enrollment gateway course

Abstract: Large enrollment foundational courses are perceived as "high stakes" because of their potential to act as barriers for progression to the next course or admittance to a program. The nature of gateway courses makes them ideal settings to explore the relationship between anxiety, pedagogical interventions, and student performance. Here, two-stage collaborative examinations were implemented to improve test-taking skills and address widespread test anxiety in an introductory human anatomy course. Test anxiety data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Before taking the two-stage exam, 73% of the students thought that the group retake of the exam could potentially improve their grades, but after the group exam 89% of them reported that they found the group retake to be a helpful strategy to enhance their performance. This agrees with previous studies that suggest a lower level of test anxiety in group exams as a reason for improved performance [11]. Interestingly, and contrary to other reports of group exams, after compensating for marking discrepancies between markers, just over 10% of students did better on the individual portion of the exam than on the group portion (data not shown).…”
Section: Team Worksupporting
confidence: 92%
See 1 more Smart Citation
“…Before taking the two-stage exam, 73% of the students thought that the group retake of the exam could potentially improve their grades, but after the group exam 89% of them reported that they found the group retake to be a helpful strategy to enhance their performance. This agrees with previous studies that suggest a lower level of test anxiety in group exams as a reason for improved performance [11]. Interestingly, and contrary to other reports of group exams, after compensating for marking discrepancies between markers, just over 10% of students did better on the individual portion of the exam than on the group portion (data not shown).…”
Section: Team Worksupporting
confidence: 92%
“…These collaborative tests most often take the form of two-stage group exams, in which students first complete a traditional individual exam, worth the majority of their exam mark, and immediately afterwards complete the same or a very similar exam in groups, during which time they have the opportunity to discuss the material and receive immediate feedback from their peers [10]. These discussions during the group portions of the exam have been shown to present valuable opportunities for students to share their knowledge [11], practice justifying their reasoning and thought-process for each answer [12], learn from their peers, and practice their communication skills [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on the broad positive experience for the individual, such as in a medical education psychiatry test where students learnt both about the subject matter and themselves through the interpersonal dynamics of the situation 53 . Other studies showed the clear advantage even for the strong students in the class, 38,54 but effect on stress and anxiety seem to have somewhat mixed outcomes 54,55 …”
Section: Discussionmentioning
confidence: 99%
“…53 Other studies showed the clear advantage even for the strong students in the class, 38,54 but effect on stress and anxiety seem to have somewhat mixed outcomes. 54,55 Students also proposed suggestions to improve the two-stage examination. Three aspects were highlighted: (a) better time allocation for each section of the two-stage examination; (b) better space allocation for different discussion groups; and (c) introduction of more open-ended questions suitable for group stage of two-stage examination.…”
Section: Discussionmentioning
confidence: 99%
“…As detailed in a recently published article (Fournier, Couret, Ramsay, & Caulkins (), some students experienced reduced test anxiety, although this result was not universal. Nonproductive grade rates were reduced from 23% during the 2012–2013 academic year to 13% during the intervention, and to 15% in the subsequent two semesters.…”
Section: Three Cases Of Gateway‐course Faculty Developmentmentioning
confidence: 91%